1990
DOI: 10.1111/j.2044-8341.1990.tb01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's first experiences of childbirth: Two hospital settings compared

Abstract: This study analyses expectations, experiences and the aftermath of childbirth from interviews conducted with 60 mothers nine months after their first child was born. Half had given birth in a 'family birthing centre' (FBC) and half had used the conventional delivery suite (CDS). Findings showed that the two groups of women had different antenatal orientations to the birth, different experiences of the labour, different experiences of motherhood and different levels of satisfaction with childbirth in retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
5

Year Published

1992
1992
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
(13 reference statements)
4
8
0
5
Order By: Relevance
“…For example, past researchers have shown that women who choose midwives as their care providers report higher levels of Internal HLC and lower Powerful Others and Chance HLC than women who choose obstetricians (Aaronson, 1987; Littlefield & Adams, 1987). Women who choose birthing centers rather than hospitals also tend to expect more personal involvement in the birth process (Bradley, Tashevska, & Selby, 1990). Thus, the purpose of this article is to describe the development and initial psychometric properties of such a scale, which we call the Multidimensional Health Locus of Control Scales for Labor and Delivery (MHLC‐LD).…”
mentioning
confidence: 99%
“…For example, past researchers have shown that women who choose midwives as their care providers report higher levels of Internal HLC and lower Powerful Others and Chance HLC than women who choose obstetricians (Aaronson, 1987; Littlefield & Adams, 1987). Women who choose birthing centers rather than hospitals also tend to expect more personal involvement in the birth process (Bradley, Tashevska, & Selby, 1990). Thus, the purpose of this article is to describe the development and initial psychometric properties of such a scale, which we call the Multidimensional Health Locus of Control Scales for Labor and Delivery (MHLC‐LD).…”
mentioning
confidence: 99%
“…Nicht die Störung selbst, sondern ihre jeweilige Bedeutung sind entscheidend (Salmon 1992) Als weiterer Faktor wird neben unspezifischen Ängsten die Dauer der Geburt post partum negativ bewertet (Wotani 1980, Beck 1994, Möller 1995, Kentenich 1999, Stadlmayr 2001 (Green 1990, Bradley 1990, Bramadat 1990, Mackey 1990, Byrne-Lynch 1991, Slade 1993. Nachdem Vorhersehbarkeit andererseits wie bei den geburtshilflichen Abläufen nur schwer herstellbar ist, geht es mit Sicherheit auch darum, inwieweit Frauen die Kompetenz haben, auf bewährte Bewältigungsstrategien zurückzugreifen (Mackey 1990, Byrne-Lynch 1991, Peirce 1994).…”
Section: Diskussion Der Ergebnisse Der Erweiterten Perinatalerhebungunclassified
“…Nachdem Vorhersehbarkeit andererseits wie bei den geburtshilflichen Abläufen nur schwer herstellbar ist, geht es mit Sicherheit auch darum, inwieweit Frauen die Kompetenz haben, auf bewährte Bewältigungsstrategien zurückzugreifen (Mackey 1990, Byrne-Lynch 1991, Peirce 1994). Antonovsky spricht in diesem Zusammenhang vom sogenannten Kohärenzgefühl (Martinez 1993, Hallgren 1995, Antonovsky 1997 , Ringler 1991, Bramadat 1993, DiMatteo 1993, Waldenström 1996 (Green 1990, Bramadat 1990, Bradley et al 1990, Mackey 1990, Byrne-Lynch 1991, Slade 1993.…”
Section: Diskussion Der Ergebnisse Der Erweiterten Perinatalerhebungunclassified
See 2 more Smart Citations